Tax-induced trading around ex-dividend days - Lakonishok, Josef; Vermaelen, Theo (Journal of Financial Economics, 1986)
This paper investigates trading volume around ex-dividend days. For taxable distributions (cash dividends), it is found that trading volume increases significantly around the ex-dividend day. This increase is more pronounced for high yield, actively traded stocks and after brokerage commissions became negotiable. The results are consistent with the hypothesis that short-term traders have an impact on ex-day price behavior, at least for taxable distributions. For non-taxable distributions (stock splits and stock dividends) we find negative abnormal volume around ex-day.